Osteopontin regulation by protein kinase B (Akt) in HepG2 cells - Zhang, G.; Huang, Z.; Shi, R.; Lin, Y.; Hao, B. (Experimental Oncology, 2006)
Aim: The mechanism responsible for osteopontin regulation is not understood in HepG2 cells. The aim of this study was to investigate the relationship between protein kinase B (Akt), a key gene in PI3K signal transduction pathway, and osteopontin expression. Methods: HepG2 cells were transfected with constitutively active Akt and dominant negative Akt using lipofectin. The Akt transfection was confirmed by Western blot analysis. Osteopontin expression was detected by both Northern blot and Western blot. Results: Overexpression of exogenous Akt was detected in HepG2 cells by Western blot, indicating that HepG2 cells were successfully transfected with the Akt genes. In serum-free condition, the expression of osteopontin was either low or undetectable in HepG2 cells transfected with vector only, however, the expression increased after transfection of cells with constitutively active Akt. Osteopontin expression decreased when HepG2 cells were transfected with dominant negative Akt. Conclusion: Protein kinase B (Akt) gene regulated osteopontin expression in RNA level and protein level, suggesting that osteopontin synthesis can be blocked by inactivation of the Akt gene. This leads to a potential means of intervention for the inhibition of metastases in liver cancer. Цель: механизм регуляции экспресии остеопонтина еще детально не изучен. Целью данного исследования было изучение
взаимосвязи между протеинкиназой В (Akt), ключевым геном PI3K пути сигнальной трансдукции, и экспрессией остеопон-
тина. Методы: при помощи липофектина клетки HepG2 трансфецировали конститутивно экспрессирующимся геном Akt
и доминантно негативным геном Akt. Akt-трансфектанты отбирали при помощи Вестерн-блоттинга. Детекцию экспрессии
остеопонтина осуществляли методами Нозерн- и Вестерн-блоттинга. Результаты: эффективность трансфекции была
подтверждена выявленной гиперэкспрессией экзогенного гена Akt в клетках линии HepG2. В условиях культивирования
в бессывороточной среде экспрессия была низкой или даже ниже уровня детекции в клетках линии HepG2, трансфици-
рованных только вектором; тем не менее, уровень экспрессии этого белка возрастал после трансфекции клеток консти-
тутивно экспрессирующимся геном Akt. Экспрессия остеопонтина снижалась после трансфекции клеток линии HepG2
доминантно негативным геном Akt. Выводы: ген протеинкиназы В регулирует экспрессию остеопонтина на уровне РНК и
белка. Предполагается, что его синтез может быть блокирован путем инактивации гена Akt.